Economic evaluation of OROS® hydromorphone for chronic pain: A Pan-European perspective - Hauber, PhD, A. Brett; Fleischmann, PhD, Jochen; Lothgren, PhD, Mickael; Wilson, MSPH, Michele; Lam, MHEcon, Annette; Dubois, MD, Dominique; Sabatowski, MD, Rainer (Journal of Opioid Management, 2018)
Objectives: OROS® hydromorphone (osmotic extended-release oral delivery system [OROS] hydromorphone) is a long-acting opioid analgesic, which is approved in Europe for the management of severe pain. The authors aimed to estimate the economic value of this product relative to other widely used oral opioids, including sustained-release morphine, extended-release (ER) oxycodone, and twice-daily (bid) hydromorphone. Design: An adaptable, decision-analytic cost-utility model was developed. Separate versions of the model were developed for five European countries: Germany, Denmark, Slovakia, Portugal, and Italy. Results: OROS hydromorphone represents a cost-effective alternative to other strong oral opioids in the treatment of both nonmalignant and malignant pain in all five countries. In the treatment of chronic severe nonmalignant pain, OROS hydromorphone was dominant (ie, lower cost and incremental quality-adjusted life years gains) when compared with ER oxycodone in Denmark and bid hydromorphone in Germany. Likewise, OROS hydromorphone was dominant in the treatment of chronic severe malignant pain when compared with ER oxycodone in both Germany and Denmark and when compared with bid hydromorphone in all markets where hydromorphone was marketed. Conclusions: This model demonstrates the cost effectiveness of OROS hydromorphone relative to other strong oral opioids in the treatment of chronic severe malignant and nonmalignant pain.